DAMPAK COVID 19 TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR BARANG KONSUMEN – NON PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewi Oktary; Amelia Amelia (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2021)
This study aims to determine the impact of covid 19 on the financial performance of non-primary consumer goods sector companies. This study examines financial performance before and after covid 19. Financial performance is measured using the liquidity ratio, leverage ratio, activity ratio and profitability ratio. The samples in this study were non-primary consumer goods sector companies listed on the main board as many as 43 companies. The data analysis method used is the average difference test using the Wilcoxon test. The results of the analysis are that there is no difference in the average liquidity ratio before and after the occurrence of covid 19. And there is a difference in the average leverage ratio, activity ratio and profitability ratio.